Indices of accelerated erythropoiesis during a 6-day cycle race - Martin, D. T.; Boston, T.; Parisotto, R.; Gore, J. C.; Horvath, N.; Ashenden, M. J.; Craig, N.; Emslie, K.; Mangin, P.; Saugy, M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The use of recombinant human erythropoietin (rhEPO) by athletes is prohibited. This synthetic hormone is administered intramuscularly and is cleared rapidly from the circulation (2-4 days), rendering it difficult to detect. As a result, attention has been directed towards indirect markers of enhanced erythropoietic activity that may persist long after drug administration has ceased. To date, some haematological and biochemical parameters have been identified that may be useful in detecting rhEPO use. These parameters include: Haematocrit (Hct), Haemoglobin (Hb), Erythropoietin (EPO), Soluble Transferrin Receptors (sTfR), % Macrocytic Cells (%Macro), %Hypochromic Cells (%Hypo), Absolute Reticulocyte number (Ret#), Reticulocyte size (MCVr), and Mean Reticulocyte Haemoglobin Concentration (CHCMr). The purpose of this study was to examine under race conditions, those haematological and biochemical parameters, which have the potential to detect rhEPO use. Top Australian Male Road Cyclists (CYC, n=21) were monitored throughout an international calibre stage race in order to establish preliminary reference intervals with ecological validity. The 6-day race required CYC to complete 762 km (19 hrs) of racing. Control subjects (CON, n=6) exercised for less than 2 hr per day. Fasting venous blood samples (10 ml) were collected from CYC and CON each morning of the race (D1-D6). Whole blood was analysed for Hct, Hb and Reticulocyte parameters (Bayer Technicon H3) within 15 hours of collection. Serum samples were frozen for subsequent analysis of EPO and sTfR (R&D Systems, ELISA). In CON, none of the monitored parameters changed significantly. In CYC racing did not significantly change %Hypo, %Macro, MCVr, or CHCMr. However, racing was associated with the following significant changes from D1: Hct-¯ 6.6%, Hb-7.4%, Ret#-¯ 13.7%, sTfR-¯ 13%, and EPO- 30%. Results from CYC were used to establish preliminary reference intervals under race conditions; EPO [1.0-20.0 mU.ml-1], sTfR [11-30nM], Hct [38-50%], Hb [12-17 g.dL-1], %Macro [0.1-3.0%], %Hypo [0.3-4.5%], Ret# 20-90], MCVr [96-130] fL, and CHCMr [24.0-32.4] g.dL-1. Consideration should be given to the effects of racing on reference intervals when identifying potential indirect techniques for detecting EPO use.